Pengaruh Aktivitas Fisik terhadap Kebugaran Siswa SMP IT Almunadi Medan - M Fadlin Al Farhans; Mesnan; Nurhayati Simatupang (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to determine the effect of physical activity on the fitness of students at SMP IT Almunadi Medan. The research method used is a quasi-experimental, with a "Two-Group Post-test Design" design, namely an experiment that uses post-test data from the control class and the experimental class to compare the conditions of the class given treatment and the class that was not given treatment. The reasons for consideration in determining the sample are: 1) male, 2) class VII-2. Two-Group Post-test Design is an experiment conducted on two classes, namely the control class and the Experiment class. The experiment uses fun gymnastics and the control uses SKJ gymnastics. The conclusion in this study is From the results of the calculations above, it can be seen that t count is 7.5 and t table is 2.39 at a significance level of 95% or α = 0.05. Because t count> t table (7.5> 2.39), the alternative hypothesis of the study (Ha) is accepted. That there is a significant influence of Physical Activity (Rhythmic Gymnastics) on the Physical Fitness of Students of SMP IT Almunadi. From the control class data, it was obtained that respondents with the less category numbered 16 people, the very less category 1 person and the moderate category numbered 3 people. From here it can be concluded that the TKJI category for the control class is less. Based on the results of the study, the conversion value with the category in the experimental class is that with the very good category there is 1 person, with the good category there are 4 people, with the moderate category there are 15 people. Keywords: Physical Activity, Fitness, Elementary School Students.